Información Contable De La Librería “Don Arturo” De Vinces - Valverde Valencia, Génesis Del Cisne (2018)
The present investigation was carried out in the Don Arturo Bookstore with the purpose of knowing the accounting information that is handled within this, the observed accounting processes allowed the development of the present case study. Which resulted in knowing the importance of the accounting processes of a business, since it depends on the records of both income and expenses are recorded correctly, the application of this is due to the financial statements are generated accurately and know the degree of profitability that it has, otherwise there could be difficulties. To fulfill the objective of this research, bases, guidelines and methods were taken into account that in one way or another helped to shape the present research structure, the information that will be detailed below is based on the interview with the owner of the business and in the same way we can announce that through the use of the observation and inquiry method addressed to the business it was possible to know what is the structure with which the library counts and in the same way to know what is the management that is given to each one of the resources it has. It is of great importance to know that the constant changes in the accounting field open the door for the promotion of training to obtain updated illustrations on each of the terms, standards, laws and techniques in this field, considering that this is a way to achieve your purposes with the greatest satisfaction and in the most feasible way. For the development of the present case study, various aspects such as laws and books related to the area of ​​information and accounting processes have been taken into consideration, which have been fundamental requirements when establishing the most relevant points and the same that are framed in the line of Management of the Accounting Information of the Accounting and Audit Career.